Minimally invasive neurosurgical access techniques to facilitate endovascular treatment of dural arteriovenous fistulae. (2nd January 2015) - Cowie, Christopher J. A.; Pešić-Smith, Jonathan D.; Dambatta, Shuaibu; Gholkar, Anil; Surash, Surash; Jenkins, Alistair; Mitchell, Patrick
Abstract: We report two cases of dural arteriovenous fistulae treated endovascularly, where percutaneous venous or arterial access was not suitable. In both cases, a different surgical access technique was used to allow transcranial cannulation of the appropriate venous sinus or of the varix to gain access and occlude the fistula.